Implications of regulation on bank expansion : a simulation analysis - Oldfield, George S. (Greenwich, Conn. : JAI Press, 1979)
This study starts with the existing federal and state banking structure control apparatus as a frame of reference. Second, it is important to discover whether different control instruments have a significant impact on banking structure. Third, a comprehensive choice procedure is developed to demonstrate how preferred laws and policies can be identified.
Includes index.
Includes bibliographical references: p. 127-129
ne 23/01/2019
Loans
Keywords: Banks and banking; Banking regulation